2019
DOI: 10.7554/elife.44837
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of tonotopic ventral medial geniculate body is behaviorally relevant for speech recognition

Abstract: Sensory thalami are central sensory pathway stations for information processing. Their role for human cognition and perception, however, remains unclear. Recent evidence suggests an involvement of the sensory thalami in speech recognition. In particular, the auditory thalamus (medial geniculate body, MGB) response is modulated by speech recognition tasks and the amount of this task-dependent modulation is associated with speech recognition abilities. Here, we tested the specific hypothesis that this behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(93 citation statements)
references
References 119 publications
(202 reference statements)
3
87
3
Order By: Relevance
“…In addition to addressing the main hypothesis of the present paper, the data also allowed the testing for replication of previous findings (Díaz et al, 2012;Mihai et al, 2019;von Kriegstein et al, 2008), i.e., a test for a main effect of task (speech -speaker) in left and right MGB and a test for a correlation between speech recognition performance and main effect of task across participants in the left MGB.…”
Section: Test For Replication Of Previous Findingsmentioning
confidence: 73%
See 4 more Smart Citations
“…In addition to addressing the main hypothesis of the present paper, the data also allowed the testing for replication of previous findings (Díaz et al, 2012;Mihai et al, 2019;von Kriegstein et al, 2008), i.e., a test for a main effect of task (speech -speaker) in left and right MGB and a test for a correlation between speech recognition performance and main effect of task across participants in the left MGB.…”
Section: Test For Replication Of Previous Findingsmentioning
confidence: 73%
“…We focused on the left vMGB for two reasons. First, its response showed behavioural relevance for speech recognition in previous studies (Mihai et al, 2019;von Kriegstein et al, 2008). Second, a study on developmental dyslexia -a condition that is often associated with speech-in-noise recognition difficulties (Chandrasekaran et al, 2009;Ziegler et al, 2009) -showed reduced task-dependent modulation of the left MGB in comparison to controls (Díaz et al, 2012).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations